Liquefaction-induced settlements of residential buildings subjected to induced earthquakes. Issue 129 (February 2020) - Chaloulos, Yannis K.; Giannakou, Amalia; Drosos, Vasileios; Tasiopoulou, Panagiota; Chacko, Jacob; de Wit, Sjoerd
Abstract: The paper evaluates the dynamic performance of existing residential houses affected by gas-extraction-induced earthquakes in an area of low tectonic seismicity where structures have not been designed against earthquake loading. The foundation consists of narrow spread footings (width, B < 0.7 m), while the seismic demand is characterized by low intensity. Nonlinear, effective stress, fully coupled, dynamic soil-structure interaction analyses were performed to develop estimates of liquefaction-induced settlements for buildings on narrow spread footings, founded in a range of soil conditions, with ground motions and structural characteristics that are typically encountered in the study area. The results verify patterns observed in recent studies for slab foundations and shed light on new mechanisms. For the low magnitude earthquakes considered in this study, the total foundation settlements were found to be relatively limited, although simplified liquefaction triggering calculations would sometimes predict low factors of safety against liquefaction. A simplified equation was developed from regression of the numerical analyses results to derive estimates of liquefaction-induced settlements for residential buildings that was adopted in the latest update of the relevant seismic building code. Highlights: Liquefaction-induced settlements of low buildings from man-induced earthquakes. Advanced numerical methodology - validation against centrifuge test and case study. Estimation of both co-seismic (shear) and post-seismic (volumetric) settlements. Over 500 numerical analyses for critical soil, structure and excitation parameters. New empirical relationship for the estimation of liquefaction-induced settlements.